Effect of high temperatures on the performance of growing-finishing pigs. The case of Alentejo - Fitas da Cruz V.; Le Dividich J.; Cancela d'Abreu M. (Tradition and innovation in Mediterranean pig production, 2000)
Ambient temperature is one of the main components of the physical environment, as it is a permanent factor and one of the most important affecting the physiology, behaviour and productivity of pigs. Thus, it is of particular interest to house these animals under conditions which permit maximize their zootechnical performances. Presently it is accepted that the optimum temperature for the performance of growing-finishing pigs is between 20 degrees C and 25 degrees C. Under higher environmental temperatures, i.e., near the upper critical temperature, the carcasses are lean, but the food ingestion is severely affected, leading to a slow growth rate. In Portugal, around 17 per cent of the swine production is located in Alentejo. The purpose of this paper is to describe, using the little information available, the effect of high temperatures on growing-finishing pigs.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)